Comparison of ophthalmic artery Doppler with PlGF and sFlt‐1/PlGF ratio at 35–37 weeks' gestation in prediction of imminent pre‐eclampsia. (6th April 2022) - Lau, K.; Wright, A.; Sarno, M.; Kametas, N. A.; Nicolaides, K. H.
ABSTRACT: Objective: To compare the predictive performance for delivery with pre‐eclampsia (PE) at < 3 weeks and at any stage after assessment at 35 + 0 to 36 + 6 weeks' gestation of serum placental growth factor (PlGF) and soluble fms‐like tyrosine kinase‐1 (sFlt‐1)/PlGF ratio with that of a competing‐risks model utilizing maternal risk factors, mean arterial pressure (MAP) and ophthalmic artery peak systolic velocity (PSV) ratio. Methods: This was a prospective observational study of women attending for a routine hospital visit at 35 + 0 to 36 + 6 weeks' gestation. This visit included recording of maternal demographic characteristics and medical history, ultrasound examination of fetal anatomy and growth, assessment of flow velocity waveforms from the maternal ophthalmic arteries and measurement of MAP, serum PlGF and serum sFlt‐1. The performance of screening for delivery with PE at < 3 weeks and at any time after the examination was assessed using areas under the receiver‐operating‐characteristics curves and detection rates (DRs), at a 10% false‐positive rate (FPR). McNemar's test was used to compare DRs, at a 10% FPR, between screening by PlGF concentration, the sFlt‐1/PlGF concentration ratio and the competing‐risks model utilizing maternal risk factors, MAP and ophthalmic artery PSV ratio. Model‐based estimates of screening performance for different methods of screening were also produced. Results: The study population of 2338 pregnancies contained 75 (3.2%) cases that developed PE, including 30 (1.3%) that delivered with PE at < 3 weeks from assessment, and 2263 cases unaffected by PE. The DR of PE at < 3 weeks from assessment, at a 10% FPR, of sFlt‐1/PlGF ratio (70.0% (95% CI, 50.6–85.3%)) was superior to that of PlGF (50.0% (95% CI, 31.3–68.7%)) or PSV ratio (56.7% (95% CI, 37.4–74.5%)) but inferior to that of the combination of maternal risk factors, MAP multiples of the median (MoM) and PSV ratio delta (96.7% (95% CI, 82.8–99.9%)). Similarly, the DR of PE at any stage after assessment of sFlt‐1/PlGF ratio (62.7% (95% CI, 50.7–73.6%)) was superior to that of PlGF (52.0% (95% CI, 40.2–63.7%)) or PSV ratio (41.3% (95% CI, 30.1–53.3%)) but inferior to that of the combination of maternal risk factors, MAP MoM and PSV ratio delta (78.7% (95% CI, 67.7–87.3%)). The empirical results for DR at a 10% FPR were consistent with the modeled results, both for delivery with PE at < 3 weeks and at any time after assessment. Conclusion: Ophthalmic artery Doppler in combination with maternal risk factors and blood pressure could potentially replace measurement of PlGF and sFlt‐1/PlGF ratio in the prediction of imminent PE. © 2022 International Society of Ultrasound in Obstetrics and Gynecology.